2002
DOI: 10.1097/00001756-200201210-00020
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and cognitive responses to rivastigmine treatment in Alzheimer’s disease

Abstract: Twenty seven patients with mild AD were enrolled in a prospective open label controlled study of rivastigmine. Assessments included a range of neuropsychiatric and behavioural measures and rCBF using HMPAO SPECTat baseline, three and six months. Significant enhancement of frontal, parietal and temporal brain blood flow with related psychometric improvement was observed in twelve of the treated patients. A pattern of reduced rCBF and cognitive performance was observed in four unresponsive and eleven untreated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 17 publications
6
72
0
Order By: Relevance
“…The increased metabolism in the frontal and parietal regions after ChEI treatment in our study looks similar to the short-term perfusion change pattern seen in response to ChEIs in patients with AD, except for the metabolic or perfusion changes in the temporal area (33,34). Because all patients in this study had a lower cardiac MIBG uptake score (in the PD range at our institute), and patients with AD are known to have a reference range of cardiac MIBG uptake (35), it is less likely that patients with AD would have been included in our study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The increased metabolism in the frontal and parietal regions after ChEI treatment in our study looks similar to the short-term perfusion change pattern seen in response to ChEIs in patients with AD, except for the metabolic or perfusion changes in the temporal area (33,34). Because all patients in this study had a lower cardiac MIBG uptake score (in the PD range at our institute), and patients with AD are known to have a reference range of cardiac MIBG uptake (35), it is less likely that patients with AD would have been included in our study.…”
Section: Discussionsupporting
confidence: 83%
“…However, recent functional imaging and neuropathologic data demonstrated that the burden of AD-like pathology and the density of Lewy bodies are more severe in DLB than in PDD (6,31,32), suggesting different pathologic backgrounds for the 2 diseases. Thus, on the basis of our data and those of another study, we speculate that at least the anatomic substrate for the response to ChEIs in patients with PDD may be different from those with DLB, although this difference does not directly indicate a different nature of disease between PDD and DLB.The increased metabolism in the frontal and parietal regions after ChEI treatment in our study looks similar to the short-term perfusion change pattern seen in response to ChEIs in patients with AD, except for the metabolic or perfusion changes in the temporal area (33,34). Because all patients in this study had a lower cardiac MIBG uptake score (in the PD range at our institute), and patients with AD are known to have a reference range of cardiac MIBG uptake (35), it is less likely that patients with AD would have been included in our study.…”
supporting
confidence: 46%
“…Generally, a good correlation between cognitive changes and perfusion/ metabolism changes was found, i.e. stabilization or even improvement of perfusion and metabolic abnormalities was paralleled by a slowing of further deterioration or even improvement of cognitive function (61)(62)(63)(64)(65)(66)(67)(68). Recently, 11 C-labeled compounds which pass the blood-brain barrier and bind with high affinity to fibrillar amyloid plaques have been developed and allow for the first time in vivo quantification of the amyloid burden (69).…”
Section: Pet and Spect In Ad Treatment Trialsmentioning
confidence: 88%
“…In these studies, the frontal, temporal and/or parietal cortices were particularly affected by the treatment, whereas an overall increase was also observed. Differential effects in AD patients responding or not responding to treatment with donepezil or rivastigmine were also demonstrated (Potkin et al, 2001;Nobili et al, 2002a;Vennerica et al, 2002).Aged rhesus macaques (Macaca mulatta) are considered to be a good model for human aging because of their characteristic behavioral and pathological features. Rhesus macaques were reported to develop age-associated impairments in performance on cognitive/memory tasks, and in their late teens, some animals show impairments in performance of certain spatial abilities, whereas senile plaques and amyloid deposArticle, publication date, and citation information can be found at…”
mentioning
confidence: 96%
“…PET studies in AD have shown that reductions in rCBF and rCMRglc correlate with cognitive decline and the appearance of pathological changes (Friedland et al, 1985;DeCarli et al, 1992;Harkins et al, 1997;Jagust et al, 1997). Furthermore, clinical studies have reported attenuation of AD-related metabolic and perfusion deficits in patients treated with a variety of cognitive enhancers such as tacrine (Nordberg et al, 1998), physotigmine (Tune et al, 1991), donepezil (Staff et al, 2000;Nobili et al, 2002a,b), and rivastigmine (Potkin et al, 2001;Vennerica et al, 2002;Tune et al, 2003). In these studies, the frontal, temporal and/or parietal cortices were particularly affected by the treatment, whereas an overall increase was also observed.…”
mentioning
confidence: 99%